Knowledge transfer between SMEs and higher education institutions: the difference between universities and colleges of higher education. - Heike Delfmann; Sierdjan Koster (European Regional Science Association (ERSA), 2010)
Knowledge transfer has been widely recognized as a key element of innovation that drives competitive advantage and regional development in knowledge-driven economies. In this respect the role of institutes of higher education is essential, as they generate knowledge. The vast majority of research on the topic of transferring knowledge focuses on universities. In the case of the Netherlands however, because of their binary system, colleges of higher education make up a great deal of the complete higher education system. We argue that these colleges of higher education are better suited to address the needs of small businesses than universities. Colleges have a more practical educational approach, they are closer related to the industry, which enhances their accessibility and approachability for small firms. This paper explains the difference in knowledge transfer between the two types of higher education institutes. The main goal of this research is to provide a classification of SMEs who take part in the knowledge transfer process of specifically colleges of higher education compared to universities. This paper presents the results of a recent study using a survey among small organisations in the area of Groningen, the Netherlands. Using Groningen as a case study we were able to collect data from a region with one university and one college of higher education of similar size.
Keywords: 330; knowledge transfer; colleges of higher education; universities; SMEs